Effect of Primary Energy Consumption towards Disagregated Sectoral Outputs of India - Thurai Murugam, Nathan; Liew, Venus Khim-Sen; Abdullah, Al Mamun (Asean Research Consortium, 2013)
This paper investigates the co-integration relationship and causality effect between energy used and main economic sectors such as agriculture, services and industrial sector in India for the period of 1980-2009. The purpose of this study is to well organise the energy used among the sectors in India to achieve the optimum usage of energy and reduce the wastage. Empirical results suggest that short-run causality running from services outputs towards energy used and energy used towards agriculture outputs. There is no evidence of short-run causality effect between energy used and industrial outputs. This study revives that services outputs not depending on energy used and agriculture output’s growth mainly depending on the energy. Based on the findings, few recommendations have been suggested to well organise the energy usage wisely.